2011
DOI: 10.1063/1.3671366
|View full text |Cite
|
Sign up to set email alerts
|

Negative capacitor paves the way to ultra-broadband metamaterials

Abstract: Experimental demonstration of the overcoming of basic dispersion-energy constraints in metamaterials with the help of active non-Foster negative capacitors is reported. The experimental metamaterial operates in RF regime, and it is based on air transmission line loaded with negative capacitors. Measurement results clearly show almost dispersionless Epsilon-Near-Zero behavior, accompanied with superluminal both phase and group velocities, over a bandwidth of more than four octaves (2 MHz-40 MHz). The principle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 15 publications
5
101
0
1
Order By: Relevance
“…Both aspects have to be treated with extreme caution. Recent experiments on metamaterials composed of active non-Foster elements operating at MHz and GHz frequencies [20,21] have shown rather constant superluminal electromagnetic phase and group velocities from 2 MHz to 40 MHz frequency [21] (more than four octaves bandwidth). The frequency dependence occurring at yet higher frequencies guarantees the fundamental consistency with causality and with the laws of special relativity [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Both aspects have to be treated with extreme caution. Recent experiments on metamaterials composed of active non-Foster elements operating at MHz and GHz frequencies [20,21] have shown rather constant superluminal electromagnetic phase and group velocities from 2 MHz to 40 MHz frequency [21] (more than four octaves bandwidth). The frequency dependence occurring at yet higher frequencies guarantees the fundamental consistency with causality and with the laws of special relativity [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, considering the fact that the limited bandwidth of the detached ZIM lens arises from the highly dispersive constitutive parameters of bulky passive metamaterials, one can predict that the incorporation of active elements [35] or gain medium [36] into the metamaterial structure could enable broadband operation. In Ref.…”
Section: The Methods For Broadening the Bandwidth Of The Detached Zimlmentioning
confidence: 99%
“…In Ref. [35], S. Hrabar et al demonstrated how to overcome the dispersion constraints in metamaterials for radio frequencies with the help of active non-Foster negative capacitors. Their designed metamaterial exhibits almost dispersionless near-zero permittivity behavior over a very broad bandwidth of more than four octaves (2 MHz-40 MHz).…”
Section: The Methods For Broadening the Bandwidth Of The Detached Zimlmentioning
confidence: 99%
“…Negative capacitor is actually a source that supplies additional current to the positive capacitor [8]. This additional current causes faster charging and therefore decreases the effective capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…From the circuit theory point of view, one may say that the dispersion in passive metamaterials occurs due to the basic difference in the frequency behavior of a capacitor and an inductor. Very recently, it has been shown that, in some cases, it is possible to overcome basic dispersion constrains (1,2) by the use of electronic circuits that behave as negative capacitors or negative inductors (so-called non-Foster elements [5][6][7][8][9]). The simplest implementation (Fig.…”
Section: Introductionmentioning
confidence: 99%